The syntax of complex adding numerals and Hebrew diachrony - Screnock, J (Society of Biblical Literature, 2018)
The syntax of complex adding numerals and its apparent development in Ancient Hebrew contribute several new pieces to the puzzle of Hebrew diachrony and, consequently, to the dating of biblical texts. I describe undiscussed aspects of the structure of adding numerals and analyze the distribution of structural types according to diachrony. I also provide a diachronic analysis of the order of adding numerals that challenges the traditional position. The syntactical phenomena of adding numerals confirm the idea that the Hebrew in the biblical texts changed over time. Although the diachronic progression of adding-numeral syntax argues against a strict periodization of Hebrew into two stages, the evidence of adding numerals is compatible with the traditional model of Hebrew diachrony.